INVESTMENT STRATEGY AND ANALYSIS FOR GRAIN TERMINAL DEVELOPMENT A CASE STUDY: INDONESIA PORT CORPORATION (The Indonesian Journal of Business Administration, 2019)
The purpose of this research is to conduct a feasibility study related to the development of grain terminal at one of sea ports owned by Indonesia Port Corporation. This study aims to determine the most appropriate investment strategy both in normal market trend and within condition when there is a trend breaker. The study will answer the question of what alternative strategies are available to carry out development plan. Which is the best investment strategy based on Net Present Value (NPV), Internal Rate of Return (IRR), Pay Back Period (PBP) and Value at Risk under normal market trend? Which is the best investment strategy based on NPV within condition when there is a trend breaker? Exploration begins with an analysis of the business situation using PESTLE analysis, competitor analysis, port capacity analysis and financial performance analysis. The SWOT & TOWS framework is then used to formulate solution scenarios, namely; (1) "as is" terminal operation, (2) single stage terminal development, (3) multi stages terminal development. In normal market trend, each scenario is then evaluated through Capital Budgeting analysis using the Discounted Cash Flow (DCF) method while Value at Risk (VaR) is evaluated using Monte Carlo Simulation. In the presence of trend breaker, Decision Tree analysis is used to evaluate the Net Present Value of each scenario. This evaluation concludes that the multi-stage development strategy produces the best value of investment criteria under normal market trends and when there is a trend breaker.Keywords: Grain Terminal,  Multi Stages, Trend Breaker, NPV,  Value at Risk.